Analisis Distribusi Tenaga Rekam Medis Dalam Pelayanan Rekam Medis Dan Informasi Kesehatan di Puskesmas Kota Serang Tahun 2016 - Detia Nurpelita Sari; Nanda Aula Rumana (Indonesian of Health Information Management Journal (INOHIM), 2016)
AbstractAvailability of qualified health personnel in adequate amounts is essential for health development in the region to achieve better health development. Related to the importance of health personnel, distribution of personnel medical records must be done evenly so that the hospital or health providers to get medical records personnel in accordance with their competence. Puskesmas (Community Health Center) is a public health care facilities are very important in Indonesia, therefore personnel medical records are needed in the health center. This study aims to determine the distribution of medical records in Puskesmas Serang city 2016 by 4 aspects of educational background, employment status, training history and length of service. research conducted in Serang city health center that was conducted in June 2016. The sampling technique using saturated samples taken from a population of 63 sebanayak personnel medical records medical records personnel. Research shows the number of medical record personnel educational background in medical records and health information by 11 (17.4%) medical records personnel, medical record number of workers whose employment status of civil servants (PNS) was 48 (76.2%) medical records personnel and Labor Contract (TKK) amounted to 15 (23.8%) medical records personnel, medical record number of workers who have a history of training in medical records amounted to 10 (15.9%) medical records personnel, stocking of average personnel medical records in Puskesmas Kota Serang have a long service life of 10 years. Expected for the recruitment of new medical records in health centers in the city of Serang next order medical records personnel who received educational background in medical records and health information.Keywords: distribution, personnel, medical record Abstrak Ketersediaan tenaga kesehatan yang bermutu dalam jumlah yang memadai sangat penting bagi pembangunan kesehatan di daerah untuk mencapai tujuan pembangunan kesehatan secara lebih baik. Terkait pentingnya tenaga kesehatan, ditribusi tenaga rekam medis harus dilakukan secara merata agar rumah sakit atau penyelanggara kesehatan mendapatkan tenaga rekam medis yang sesuai dengan kompetensinya. Puskesmas (Pusat Kesehatan Masyarakat) adalah sarana pelayanan kesehatan masyarakat yang amat penting di Indonesia oleh karenanya tenaga rekam medis sangat dibutuhkan di Puskesmas. Penelitian ini bertujuan untuk mengetahui distribusi tenaga rekam medis di Puskesmas Kota Serang Tahun 2016 berdasarkan 4 aspek yaitu latar belakang pendidikan, status kepegawaian, riwayat pelatihan dan lama masa kerja. penelitian dilakukan di puskesmas Kota Serang yang dilaksanakan pada bulan Juni 2016. Teknik pengambilan sampel menggunakan sampel jenuh yang diambil dari populasi tenaga rekam medis sebanayak 63 orang tenaga rekam medis. Hasil Penelitian menunjukan jumlah tenaga rekam medis yang berlatar belakang pendidikan rekam medis dan informasi kesehatan sebanyak 11 (17,4%) orang tenaga rekam medis, Jumlah tenaga rekam medis yang berstatus kepegawaian Pegawai Negeri Sipil (PNS) berjumlah 48 (76,2%) orang tenaga rekam medis dan Tenaga Kerja Kontrak (TKK) berjumlah 15 (23,8%) orang tenaga rekam medis, Jumlah tenaga rekam medis yang mempunyai riwayat pelatihan tentang rekam medis berjumlah 10 (15,9%) orang tenaga rekam medis, Rata-rata tenaga rekam medis di Puskesmas Kota Serang mempunyai lama masa kerja 10 tahun. Diharapkan untuk penerimaan tenaga rekam medis baru di Puskesmas di Kota Serang selanjutnya agar tenaga rekam medis yang diterima beratar belakang pendidikan rekam medis dan informasi kesehatan.Kata Kunci : Distribusi, Tenaga , Rekam Medis.